2017
DOI: 10.1139/facets-2016-0031
|View full text |Cite
|
Sign up to set email alerts
|

Substrate utilization by endophytic bacteria Paenibacillus polymyxa P2b-2R that may facilitate bacterial entrance and survival inside diverse plant hosts

Abstract: Bacterial endophytes are thought to enter plants either through pre-existing openings in plant tissues or by creating openings by hydrolyzing major plant cell wall components. A lodgepole endophyte, Paenibacillus polymyxa P2b-2R, consistently formed endophytic colonies when inoculated in diverse plant hosts, viz., lodgepole pine, western red cedar, corn, canola, and tomato. We were interested to know, whether or not this bacterial strain possesses enzymes that can hydrolyze three major plant cell wall componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…we were able to isolate a much higher number of endophytic bacteria that showed positive N-fixing ability in ARA. This is consistent with the results of Yang et al (2016Yang et al ( , 2017 (Tables 1 and 2). These…”
Section: Discussionsupporting
confidence: 92%
“…we were able to isolate a much higher number of endophytic bacteria that showed positive N-fixing ability in ARA. This is consistent with the results of Yang et al (2016Yang et al ( , 2017 (Tables 1 and 2). These…”
Section: Discussionsupporting
confidence: 92%
“…After the incubation period, the agar was flooded with Congo red solution (0.5% w/v) for 30 min, drained, and then rinsed with 1 mol/L NaCl (Yang et al 2017). The clear zone around the bacterial colony indicated cellulose degradation.…”
Section: Qualitative Analysis Of Plant Growth Promoting Traitsmentioning
confidence: 99%
“…In this study results showed most of the isolates identified to be Bacillus species, for example, isolate GSN1XGroot from the roots of Xylocarpus granatum collected from Gazi bay expressed presence of amylases, caseinases, cellulases and chitinases suggesting a possible ecological role of these enzymes in the symbiotic relationship of the isolates and the host plants [23].…”
Section: Discussionmentioning
confidence: 57%